Enantioselective Synthesis of Azaflavanones Using Organocatalytic 6‐endo Aza‐Michael Addition. Issue 5 (12th March 2014) - Cheng, Shuanghua; Zhao, Lili; Yu, Shouyun
Abstract A method to prepare highly enantioenriched azaflavanones using an organocatalytic 6‐endo aza‐Michael addition has been described. A variety of 2‐aryl‐, 2‐vinyl‐ and 2‐methylazaflavanones were prepared in good yields (53–84%) and excellent enantioselectivities (97.6:2.4 to 99.3:0.7 er). <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>